Malay Mail , 30 April 2009 (The New Straits Times Press (M) Bhd, 2009)
The Mexican swine flu virus is a mixture of four different strains: North American swine Flu, North American avian flu, human A/H1N1 flu and swine flu strain found in Asia and Europe.